Gender and work :international perspective - Sita Vanka,Ed; Rekha Pande,Ed; Bharat Chillakuri,Ed (Rawat, 2019)
Gender could be understood as a construct, which enables men and women to conduct themselves in a characteristic style and helps them understand their respective roles in family and society. Gender operates at all levels of social life and is deeply embedded to how work is organized, rewarded and experienced. Sociological studies on gender and work emerged during 1960s and 1970s as the women's labour force participation increased and the women's movements shifted focus on gender equality at home and at work. This field evolved over time conceptual frameworks were developed and empirical focus shifted in response to economic and societal changes. Taking clue from the research, an attempt has been made to discuss, deliberate and present multiple perspectives in a volume showcasing the best practices, research papers and viewpoints from across the world. The contributors of this volume have covered a variety of subjects encompassing gender and work, which broadly include issues of gender equality, gender relations, women's livelihoods, gender disability, economic empowerment etc. both from Indian and international perspectives. The book provides an excellent opportunity to professionals, scholars and researchers interested to update their knowledge on the concept, processes, issues and emerging paradigms on gender and work from a multi-dimensional cross-country perspective.